Changes of Nitric Oxide and Peroxynitrite Serum Levels during Drug Therapy in Patients with Obsessive-Compulsive Disorder. (16th October 2016) - Kouti, Leila; Sayyah, Mehdi; Mosallanezhad, Parisa; Kooti, Sara; Aghakoochakzadeh, Maryam; Eslami, Kaveh
Abstract : Objectives . Some studies have shown that increased nitric oxide (NO) concentrations may be associated with obsessive-compulsive disorder (OCD). In a few animal researches, enhanced synthesis of NO had reversed the effect of selective serotonin reuptake inhibitors (SSRIs). The present study tries to find the effect of treatment with SSRIs on NO serum levels and its product peroxynitrite. Patients and Methods . Patients diagnosed with OCD who are candidates of receiving SSRIs entered this study. Two blood samples were taken from subjects, prior to drug therapy and after the patients had shown some improvements due to their regimen. Serum NO and peroxynitrite levels were measured and their correlation with SSRI use was assessed. Results . 31 patients completed this study. Mean concentrations of NO and peroxynitrite prior to drug therapy were28.63 ± 16.9 and5.73 ± 2.5   μ mol/L, respectively. These values were 18.87 ± 7.55 and2.15 ± 0.94   μ mol/L at the second blood test. Withp values < 0.05, these differences were considered significant. Conclusion . Patients, who showed improvement of OCD symptoms after a mean duration of SSRI monotherapy of3.531 ± 0.64 months, had lower values of NO and peroxynitrite in their sera compared to their levels prior to therapy. Such results can be helpful in finding a predictive factor of response to therapy and augmentation therapy with future drugs that target NO synthesis.